Characterization of the rubber tree metallothionein family reveals a role in mitigating the effects of reactive oxygen species associated with physiological stress. (7th February 2018) - Huang, Yacheng; Fang, Yongjun; Long, Xiangyu; Liu, Linya; Wang, Jia; Zhu, Jinheng; Ma, Yanyan; Qin, Yunxia; Qi, Jiyan; Hu, Xinwen; Tang, Chaorong
Abstract: Metallothioneins (MTs) as reactive oxygen species (ROS) scavengers play important roles in stress response and heavy metal homeostasis. In Hevea brasiliensis (the para rubber tree that is the source of commercial natural rubber) and in other trees, the functions of MTs are not well understood. Latex exudes when the rubber tree is tapped. The flow of latex and its regeneration can be enhanced by tapping, wounding and ethylene treatment, all of which produce ROS as a by-product. Here, we show the presence of four MT genes in H. brasiliensis, comprising three Type 2 ( HbMT2, - 2a and - 2b ) and one Type 3 ( HbMT3L ) isoforms, representing one of the smallest MT gene families among angiosperms. The four HbMTs exhibited distinct tissue expression patterns: HbMT2 and HbMT3L mainly in leaves, HbMT2a specifically in flowers and HbMT2b in diverse tissues. The expression of HbMT2b, an isoform present in latex, decreased significantly in the latex following the stress-inducing treatments of tapping, wounding and ethephon (an ethylene generator). The expressions of the leaf-abundant isoforms, HbMT2 and - 3L were up-regulated following pathogenic fungus infection and high-temperature stress, but down-regulated by low-temperature stress. These reactions were consistent with multiple defense- and hormone-responsive cis -acting elements in the HbMT promoters. Nine transcription factors were shown to implicate in the high-temperature responsiveness of HbMT2 and - 3L in leaves. Overexpression of HbMT2 in Escherichia coli enhanced the bacterium's tolerance to heavy metals and ROS, consistent with its predicted role as an ROS scavenger. Taken together, our results, along with other relevant studies, suggest an important role of HbMTs in latex regeneration as well as species adaptation via the regulation of ROS homeostasis.